David Mitchell's Cloud Atlas : "revolutionary or gimmicky?" : a thesis presented in partial fulfillment of the requirements for the degree of Master of Arts in English at Massey University, Manawatu, New Zealand - Johnston-Ellis, Sarah Jane (Massey University, 2010)
This thesis will examine David Mitchell’s use of postmodern narrative structures and strategies in Cloud Atlas and how these relate to his overtly political concerns regarding relations of power between individuals and between factions. This will involve a discussion of debates surrounding the political efficacy of postmodern narrative forms. I will consider Mitchell’s prolific use of intertextual and intratextual allusion and his mimicry of a wide range of narrative modes and genres. These techniques, along with the complex structural iterations in the novel and the ‘recurrence’ of characters between its parts, appear to reinforce a thematic concern with the interconnectedness — indeed, the repetition — of human activity, through time and a fatalistic conception of being that draws on two central Nietzschean notions, eternal recurrence and the will to power. The vision of humanity and human relations of power that is expressed within Cloud Atlas is open to extended analysis in Foucauldian terms. Against this apparently nihilistic backdrop, Mitchell appears to promote a notion of (albeit limited) individual agency and the capacity for creative narration and reinterpretation of the past as a means to devise new ‘truths’ and explore new ‘meanings’ for the present and the future. I will explore the ways in which Mitchell’s metafictional self-reflexivity (and that of his protagonists), offers a vision of hope and political agency that counters the apparent (Nietzschean) fatalism of the novel.
Keywords: David Mitchell; 'Cloud Atlas'; Fields of Research::420000 Language and Culture::420200 Literature Studies::420204 British and Irish